Profile of congenital heart disease and its mode of presentation in children admitted in a tertiary care hospital: a cross-sectional study - Mallick, M. Suhail Alam; Jana, Jadab Kumar; Maiti, Swarupananda; Pal, Abhay Charan (International Journal of Contemporary Pediatrics, 2024)
Background: Congenital heart disease (CHD) is contributing more to the infant mortality rate these days. Therefore, we must investigate the profiles of CHD, it’s presenting clinical features, and its consequences to assist pediatricians and cardiologists in taking the necessary actions as soon as possible to reduce infant mortality further. Methods: This cross-sectional study was carried out on 111 infants with CHD who were admitted to the Bankura Sammilani Medical College and Hospital’s pediatric medicine department in Bankura, India. The children ranged in age from one month to five years. Following approval by the Institutional Ethics Committee and parental/guardian consent, we used a case record proforma to gather data on enrolled children over ten months. To analyze the data, EpiInfo (version 3.5.1) software was used. This study received approval from the Institutional Ethics Committee. Result: Male children contributed 53.15%, while female children contributed 46.85%. Children between the ages of one and six months made up 55.86% of the total. Among cardiac lesions, acyanotic CHD was more prevalent than cyanotic CHD (81.08% vs. 18.92%). In all cases of CHD, the most prevalent lesion type was ventricular septal defect (VSD) (43.24%). The most prevalent form of cyanotic CHD, however, was the tetralogy of Fallot’s (9.9%). Most of the children with atrial septal defects presented in late infancy. Inadequate weight gain (85.59%) and malnutrition (84.68%) were the most prevalent clinical characteristics and complications of CHD. Conclusion: The most common complication of CHD in children under five is malnutrition, a risk factor for infant death. Hence, a community-based case-control study is essential to determine the precise extent of these burdens.